Influence of topography in flooding events in the city of Maringa, Parana - Garcia, Carolina; Marques, Verônica Ricken; Pereira, Priscila Pini; Pompeu, Cassia Rocha; Okawa, Cristhiane Michiko Passos; Ildefonso, Jesner Sereni (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Developing countries often face environmental disasters caused by flooding, resulting in environmental and socioeconomic damage in urban areas. The topographyof the region influences the flow or water accumulation. Then, the objective of this article was to provide the hypsometric mapfrom Maringá, Paraná check if there is influence of its topographyin the event of flooding. For this purpose, flooding occurrences data were acquired by the Fire Department from Maringá. It was used satellite images provided by the USGSsite and the softwareArcGIS 10to createthe Land Use and Elevation maps of Maringá and the flooding points were overlapped and depicted. Three study areaswere chosen and their hydrographic sub-basinswere drawn. Insub-basin 1,points of flooding were in the central portion;insub-basin 2, points wereconcentrated at basin-head; and in sub-basin 3, points were in the centerregion. After hypsometric mapanalysis, the conclusion was that flooding in Maringá occurs independentof the topographical position.